Assessment of Chemical Residues, Heavy Metals, and Antioxidant Activity in Marigold Flowers Grown in Betong District, Yala Province, and Development of Cosmetic Products from Marigold Flowers - Lateh, Likit; Haron, Wankassama; Khongsichan, Ladawan; Matchawet, Suradet; Muhamad, Nisaporn (YRU Journal of Science and Technology, 2025)
The marigold flower contains a variety of bioactive compounds, particularly with antioxidant properties. Utilizing downgraded marigold flowers during the production process and converting them into cosmetic products is an interesting option for adding value to local raw materials. The aim of this research was to investigate the total phenolic content and antioxidant properties of graded and downgraded marigold flowers from Betong District, Yala Province, Thailand, for the development of cosmetic products. The analysis of residual chemicals and heavy metals in the soil and marigold flowers revealed that no residual chemicals were found in either the soil or the flowers. Additionally, the levels of heavy metals were within the standard limits. Subsequently, both the graded and downgraded marigold flowers were extracted by maceration with ethanol as the solvent. The total phenolic compounds and the antioxidant activity were evaluated. The results showed that the total phenolic compounds in the crude marigold flower extract are higher than in the graded marigold flowers, with a value of 4.521±0.064 mg GAE/g extract, and an antioxidant activity (IC50) of 0.819±0.042 mg/ml, which is significantly different from the graded marigold flowers. Furthermore, the basic properties of liquid body wash and shampoo products containing marigold flower extract were examined, revealing a pH value between 5 and 6, good stability, no separation, no microorganisms or fungi, and good flow ability. Therefore, it can be concluded that downgraded marigold flowers can be developed into cosmetic products, which adds value and provides an alternative source of income for farmers.